Tracking SDG7 : The Energy Progress Report 2022 (International Renewable Energy Agency IRENA, 2022)
This joint tracking report provides the most comprehensive look available at the world's progress towards global energy targets on access to electricity, clean cooking, renewable energy and energy efficiency.